Dream within a dream - MacLachlan, Patricia (New York : Margaret K. McElderry Books, 2019)
Eleven-year-old aspiring writer Louisa considers traveling the world with her globetrotting parents, but friendship with George helps her to see her grandparents' farm on Deer Island in a new light.
Keywords: Friendship -- Fiction; Family life -- Fiction; Farm life -- Fiction; Islands -- Fiction; JUVENILE FICTION / Family / Multigenerational; JUVENILE FICTION / Social Issues / Adolescence; JUVENILE FICTION / Social Issues / Friendship